Developing Methods and Tools for Local Target-oriented Action Selection Processes in the Transport System - Robèrt, Markus (Journal of Environmental Accounting and Management, 2026)
The Swedish Transport Administration, together with public transport providers, municipalities, transport planners, and other stakeholders, has launched a new concept for transport planning called Local Action Selection Process (LASP). The aim of LASP is to create informed decisions and consensus around alternative accessibility improvements in the transport system through a process of dialogue between public authorities and other stakeholders. On the national scale, Sweden has set some of the world’s toughest climate targets, implying a transport sector independent of fossil fuels by 2030. The aim of this study was to create a structured methodology and process format for integrating the national transport targets at a local scale in LASP by constructing quantifiable and tailor-made target scenarios. The so-called CERO model (Climate and Economic Research in Organizations) for target-oriented travel planning at organization level was reformed in this work to handle scenario generation and prioritization of measures in LASP. In addition, a simulation tool was developed to support the quantitative basis for scenario generation and decision making between stakeholders in the planning process.